First Year in Accounting – Fundamentals. First Year in Accounting – Principles (Book). - Cannon, Arthur M.; Wilde, W. J. (The Accounting Review, 1952)
Reviews two volumes of the book "First Year in Accounting," vol.1, "Fundamentals," vol.2, "Principles."